Ahmad Subhi Mansur's Thoughts on Hadith Alienation - Siregar, Idris; Sulidar; Faza, Asrar Mabrur (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2025)
Hadith plays an important role in Islamic teachings as an explanation of the Qur'an and a source of Islamic law. However, Ahmad Subhi Mansur's thinking rejects the authority of hadith and asserts that the Qur'an is the only source of Islamic law. Mansur, an academic from Al-Azhar University, developed the idea of ??Quranism which rejects hadith as a valid source of Islamic teachings. He argued that the Qur'an has covered all aspects of human life and does not require additional explanation from hadith. By referring to various verses of the Qur'an, Mansur reinterprets the concept of